Prolonged nursing in Cape fur seals (Arctocephalus pusillus pusillus) at Cape Cross colony, Namibia. Issue 3 (2nd July 2020) - Osiecka, Anna N; Fearey, Jack; Elwen, Simon; Gridley, Tess
Abstract : Extended nursing periods have been observed in some pinniped species. Here, we document multiple cases of such prolonged nursing in Cape fur seals in Namibia. Over three separate visits to the Cape Cross breeding colony, we observed five unusual nursing interactions. These included animals of estimated age from one to over three years suckling on awake and permitting females. One of these observations included two individuals (juvenile and pup) suckling simultaneously. In three out of five cases, the female sniffed the large suckling animal, and the lack of aggression suggested mutual recognition. We suggest that the most likely scenario for these observations is that the larger animals might be the mothers' offspring from the previous year maintaining contact over at least three years. Such prolonged nursing may occur in cases where the year's pup is not born, dies or is outcompeted by older siblings, which can result in large energetic advantages for the offspring, by maintaining a feeding relationship with mothers over more than one year. We suggest that animals that extend suckling over more than one year may increase their overall success, although possibly inhibiting their mother's pregnancy in a given year. Under poorer conditions, investing more in an older calf may also be more cost effective to the mother than risking a new pregnancy. However, further detailed investigation is necessary to explain extended nursing in this socially complex mammal.